Stereoselective Synthesis of Maresin-Like Lipid Mediators - Hong, Song; Lu, Yan; Morita, Masao; Saito, Shun; Kobayashi, Yuichi; Jun, Bokkyoo; Bazan, Nicolas G.; Xu, Xiaoming; Wang, Yapin (Synlett, 2019)
14S,22-Dihydroxy-docosa-4Z,7Z,10Z,12E,16Z,19Z-hexaenoic acid (maresin-L1) and 14R,22-dihydroxy-docosa-4Z,7Z,10Z, 12E,16Z,19Z-hexaenoic acid (maresin-L2) were chemically synthesized. They were identical to activated macrophage-produced counterparts and their total synthesis was highly stereoselective, as revealed by chiral LC-UV-MS/MS analysis. The synthesis involved the following steps: (1) kinetic resolution of a racemic allylic alcohol by the asymmetric epoxidation; (2) transformation of the epoxy alcohol to γ-hydroxyenal derivative; and (3) the Wittig reaction to furnish the Z-olefin.
Keywords: maresin-like; diHDHA; chiral LC-UV-MS/MS; lipid mediators; stereoselective organic synthesis